Analisis Kinerja Keuangan Pt. Garuda Food Tbk Periode 2017-2019 - Ina Baiti (Jurnal Bisnis, Manajemen, dan Ekonomi, 2020)
The purpose of this research is to know the financial performance of PT. Garudafood, Tbk period 2017-2019. The type of research used is associative research. The population in this study is a record of the financial statements of PT. Garudafood, Tbk, period 2017-2019, the sample Bustan in the study was a balance sheet report and a income statement period of 2017-2019. The type of data used in this research is the quantitative data of data obtained from PT. Garudafood, Tbk which in the form of numbers, such as financial statements, data collection techniques conducted are the study of documentation and library studies, then the data obtained is analyzed using three financial ratios namely, liquidity ratio, solvency ratio and profitability ratio. The indicators used in the analysis of financial ratios include current ratio, quick ratio, debt to total assets, debt to equity ratio, net profit margin and return on equity. Next to the Furthermore to measure the company's financial performance level using the financial ratio indicator. Based on the results of the research that has been done that the financial performance of PT. Garudafood, Tbk measured using the liquidity ratio showed an increase over the last 3 years, to the ratio of solvency has not been safe performance because for the last 3 years has a value above 100%, while the ratio of profitability for 3 years has not experienced even increased in the 40 value of So it can be said only the ratio of liquidity increased while the ratio of solvency and profitability ratio still have less good performance.